Management of common minor ailments in Qatar: Community pharmacists’ self-perceived competency and its predictors - Ahmed Mohamed Makhlouf (11278594) (2021)
Studies focused on comprehensive assessment of self-perceived competency of community pharmacists to manage minor ailments are scanty despite that self-perceived competency is a valid determinant of task performance. The objectives of the study were to assess community pharmacists’ self-perceived competency to manage fourteen common minor ailments in Qatar, and identify its significant predictors. A cross-sectional assessment of 307 community pharmacists was conducted with a pre-tested 20-item questionnaire. Self-perceived competency was assessed with nine elements on a scale of 1–10 (Maximum obtainable score: Each minor ailment = 90; each element = 140). Mann-Whitney U and bivariate logistic regression were used for data analyses. The response rate was 91.9% (282/307). The majority of the respondents were males (68.1%; 192/282), within the age range of 31–40 years (55.3%; 156/282). The minor ailments with the highest median competency score were constipation (76), and cold/catarrh (75) while travel sickness (69), and ringworm (69) had the lowest. The two condition-specific competency elements with the highest median score were recommendation of over-the-counter (OTC) medicines (115), and provision of instructions to guide its use (115). Ability to differentiate minor ailments from other medical conditions had the lowest median competency score (109). The significant predictors self-perceived competency were female gender (OR = 2.39, 95%CI: 1.34–4.25, p = 0.003), and working for chain pharmacies (OR = 2.54, 95%CI: 1.30–4.96, p = 0.006). Overall, Community pharmacists’ self-perceived competency was adequate for majority of the common minor ailments, and it was highest for constipation and cold/catarrh, and specifically for the recommendation of OTC medicines and provision of instructions to guide its use. However, diagnostic ability to differentiate minor ailments from other medical conditions with similar features had the lowest median competency score. Female gender and working in chain pharmacies were the significant predictors of self-perceived competency to manage minor ailments. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0256156